Characterization of composition traits related to organoleptic and functional quality for the differentiation, selection and enhancement of local varieties of tomato from different cultivar groups. (15th November 2015) - Figàs, Maria R.; Prohens, Jaime; Raigón, María D.; Fita, Ana; García-Martínez, María D.; Casanova, Cristina; Borràs, Dionís; Plazas, Mariola; Andújar, Isabel; Soler, Salvador
Highlights: We analyzed organoleptic and functional traits in 69 local tomato accessions. A high diversity has been found among accessions and within cultivar groups. Cherry and Penjar groups have been clearly distinct from the six other groups. Organoleptic and functional composition traits have been positively intercorrelated. Selection may result in local varieties with enhanced composition characteristics. Abstract: Tomato ( Solanum lycopersicum ) local varieties are having an increasing demand. We characterized 69 local tomato accessions from eight cultivar groups for proximate composition traits, major sugars, acids and antioxidants. A large diversity was found, with differences among accessions of almost tenfold for lycopene. Significant differences were found among cultivar group means for most traits. The Cherry and Penjar groups generally presented higher dry matter, soluble solids content, titratable acidity, taste index, β-carotene, ascorbic acid, total phenolics, and antioxidant activity that the other groups. Wide ranges of variation were found within each cultivar group. Positive correlations were found between proximate traits related to taste and antioxidants. The multivariate principal components analysis confirms the distinct profile of the Cherry and Penjar groups and the large variation within groups. The results will be useful for the differentiation, enhancement and selection of local tomato varieties with improved organoleptic properties and functional quality.